A Compact F-Slot-Enhanced PIFA Design for Dual-Band Bluetooth and WLAN Applications - Yahya Entiefa Mansour,; Abduladeem Beltayib,; Allafi Omran, (African Journal of Advanced Pure and Applied Sciences, 2025)
A dual-band PIFA operating at 2.4 and 5.2 GHz is proposed and designed in this paper for wireless communication applications. The presented antenna design integrates multiple resonant paths by utilizing slots and a shorting pin, allowing for dual-band operation while maintaining a low-profile shape factor suitable for modern mobile and embedded devices. This antenna is commonly utilized for Wi-Fi, which can provide coverage in the band range from 2.4 GHz up to 5.2 GHz, which is used for wireless networking technology. Based on this requirement, a dual-band air-inverted F antenna is proposed. The proposed structure is very small in size, and due ground plane at the backside, it has low back lob radiation. All essential performance parameters, such as return loss, bandwidth, radiation pattern, and efficiency of this design, were investigated through a well-known full-wave simulator HFSS package. Simulation results indicate that the performance parameters have promising behavior for both frequency bands. Due to its dual-band functionality, size, low back radiation, and low back radiation, it is a good candidate for wireless networks.